Analisis Inovasi Produk dan Komunikasi Pemasaran terhadap Minat Pengunjung Wonderland Adventure Waterpark Karawang - Noerbani, Cindy; Isyanto, Puji; Sumarni, Neni (Universitas Batanghari, 2024)
Wonderland Adventure Waterpark is a well-known entertainment destination among the general public, offering various types of water play attractions such as bubble baths, gorilla slides, lazy rivers, wave pools and other artificial surfing areas. The aim of this research is to find out how product innovation and marketing communications influence the interest of visitors to Wonderland Adventure Waterpark Karawang. In this research, the author uses a quantitative strategy with a descriptive and verification approach. The size of the research population involving visitor data in 2022 is 264,985 so the author decided on the sample size using the Slovin formula as 88 respondents. The results of the discussion from this research show that product development at Wonderland Adventure Waterpark received a positive response with a very high score, while marketing communication also received a positive response and was rated highly. The positive impact of product innovation and marketing communication together has an impact on visitor interest, this shows that the two complement each other in attracting visitor interest. Nevertheless, Waterpark management continues to empower product development and improve marketing communications to maintain its appeal and attract more visitors.